Progress in Pharmacokinetics, Pharmacological Effects, and Molecular Mechanisms of Swertiamarin: A Comprehensive Review - Hao-Xin Yang; Ying-Yue Hu; Rui Liang; Hong Zheng; Xuan Zhang (Cells)
Swertiamarin (SW), a natural iridoid glycoside primarily isolated from the genus Swertia, Gentianaceae family, has been extensively utilized in traditional medicine systems, including Ayurveda, Traditional Chinese Medicine, and Tibetan medicine, for treating fever, diabetes, liver disorders, and inflammatory conditions. Pharmacokinetic studies reveal that SW exhibits rapid absorption but demonstrates low oral bioavailability due to the first-pass effect. Pharmacological studies have demonstrated that SW possesses a wide range of pharmacological activities, including antioxidant, anti-inflammatory, anti-tumor, anti-diabetic, and neuroprotective activities. Our analysis demonstrates that SW exerts remarkable therapeutic potential across multiple pathological conditions through coordinated modulation of key signaling cascades, including Nrf2/HO-1, NF-κB, MAPK, PI3K/Akt, and PPAR pathways. This comprehensive review systematically consolidates current knowledge on SW’s pharmacokinetic characteristics, toxicity, diverse biological activities, and underlying molecular mechanisms based on extensive preclinical evidence, establishing a scientific foundation for future drug development strategies and potential clinical applications of the potential natural lead compound.